Styles effect of leadership, organizational culture and working motivation to work satisfaction of police sector Koto Tangah Padang - Rahmat Hamulian; Bustari Muchtar; Rosyeni Rasyid (International Conferences on Educational, Social Sciences and Technology)
This research was conducted at the police agency Koto Tangah Sector in Padang with 60 people’s population and a 58 police member for sample. The sampling technique used cluster stratified random sampling. The data used primary data and secondary data. Data processed by path analysis.The result showed that based on the data if partially obtained information that 1) the leadership style has no significant effect to the organizational culture, 2) the leadership style has significant effect to the work motivation, 3) organizational culture has no significant effect on work motivation 4) On job satisfaction, 5) organizational culture has a significant effect on job satisfaction, 6) work motivation has an effect on significant to job satisfaction of member of Resort Police of Koto Tangah in Padang. Based from the results, to increase job satisfaction required a positive organizational culture that is by encouraging members of the police to dare to innovate, pay attention to detail, oriented to the work and are aggressive and not relaxed in the work.